Sensory reweighting and self-motion perception for postural control under single-sensory and multisensory perturbations in older Tai Chi practitioners - Liu, Xiao-xia; Wang, Guozheng; Zhang, Ruixuan; Ren, Zhuying; Wang, Di; Liu, Jun; Wang, Jian; Gao, Ying (Frontiers in Human Neuroscience, 2024)
PurposeImpairment in perception and sensory reweighting could predispose older adults to falls. This exploratory study aimed to investigate the differences in sensory reweighting and self-motion perception for postural control under single-sensory and multisensory perturbations between older Tai Chi (TC) practitioners and healthy active older controls.MethodsTwenty-four TC practitioners and 23 age-matched non-practitioners were recruited in this observational study. Participants stood on a force plate with or without a foam surface (baseline), followed by 36 s of visual rotation stimuli, vestibular rotation stimuli, or reduced somatosensory input (adaptation), and then continued standing for 44 s (reintegration). The center-of-pressure (COP) trajectories and self-motion perception were recorded. COP signals were analyzed using traditional sway, multiscale entropy, and wavelet analysis methods and the time-window-of-integration model to examine the postural balance performance and the flexibility and speed of sensory reweighting.ResultsSignificant interaction effects of group with sensory perturbation and group with time window on COP parameters were observed (p < 0.05). Compared with non-practitioners, TC practitioners exhibited higher postural stability and complexity as the difficulty of standing tasks increased and smaller time windows to return to baseline levels as disturbance time evolved. Moreover, TC practitioners exhibited significantly greater weighting on unperturbed sensory systems, lower weighting on perturbed sensory systems for postural control, and higher self-motion perception ability under visual, vestibular, and visual-vestibular perturbations (p < 0.05).ConclusionLong-term TC practitioners exhibited superior postural stability and adaptability under challenging sensory perturbations, and smaller amplitudes and shorter durations of postural aftereffects over time during adaptation and reintegration. These improvements may be partly attributed to more rapid and flexible sensory reweighting and improved self-motion perception for postural control.